Andrés Fernández Martín y Francisco Espinosa Jiménez, San Rafael (Málaga). Las fosas. Febrero 1937- noviembre 1955, Antequera, Aratispi Ediciones, 2019, 850 páginas (Volumen I y II) - Brenes Sánchez, María Isabel; Vila Oblitas, Miguel (Hispania Nova, 2020)
--